Analisa Dan Perancangan Sistem Pengelolaan Dan Pendistribusian Barang-Barang Material Promosi Berbasis Web Di Kantor Depo Ruko Roxy Mas Jakarta Pt. Xl Axiata, Tbk - Syachroni; Muryan Awaludin (Jurnal Mahasiswa Informatika dan Desain, 2024)
Management data processing out of the goods is an important issue faced by companies, especially companies that have a system of inventory in running the company's operations. To support the smooth and firm performance, the need for a system that can manage the data processing, so that each job can be done quickly, neatly, safely, effectively and efficiently. Therefore, in the management of data processing out of the goods necessary to the application of information systems data processing to facilitate the entry and exit of goods inventory control inventory, and anywhere where these items out. Staff Promotions section in the warehouse depot roxy mas PT. XL Axiata Tbk has the task one of which is processing the data out of the goods and distributed promotional material and preparing reports promotional material goods that have been installed. Of these problems led to the idea to create a web-based application, in which can perform data processing of goods in promotional material, information inventory, as well as promotional material goods report is mounted. The methodology used in the making of this application is a method Prototype and an application is made to the programming language PHP and HTML, while MySQL database. While the program used to create this application is XAMPP for Windows, Photoshop, and Macromedia Dreamweaver.